AS PRODUÇÕES TEXTUAIS DOS SUJEITOS DE UMA COMUNIDADE QUILOMBOLA - IDENTIDADE, PERTENCIMENTO, CULTURA E IDEOLOGIA: O DIÁLOGO COM AS PRÁTICAS DISCURSIVAS - Thebas, Adriana de Medeiros Marcolano (2019)
This research directs the look at oral textual productions and writings of students belonging to a quilombola community. Its main objective is to identify whether social, historical, cultural and ideological issues that permeate/permeate the quilombola co